The results of hysterosalpingography in infertile women between 2008 and 2015 in the radiology clinic of Imam Reza Hospital in Mashhad - Donya Farokh Tehrani; Malihe Afiyat; Samineh Boloursaz; Shaghayegh Rahmani; Reza Mardani; Sahar Kazemi; Zahra Rezvani (Mashhad University of Medical Sciences, 2017)
Introduction: Infertility of couples has many negative psychological and social consequences for society, and the physicians always seek to find the causes and treatment for this problem. Detection and treatment of Uterine and tubal causes can reduce the incidence of infertility. Therefore, this study was performed with aim to assess abnormal findings of hysterosalpingography (HSG) in infertile couples. Methods: This descriptive study was performed on 308 women referring to the radiology clinic of Imam Reza hospital for hysterosalpingography between 2008 and 2015. A checklist was prepared from data recorded in files and reports of radiography. Data were analyzed by SPSS software (version 16). Results: During the study period, 308 infertile women referred with mean age of 30.5±6.4 years and mean duration of infertility of 2.4±2.8 years. 54% of patients had primary infertility and 46% secondary infertility. The most common pathology among the infertile women was tubo-peritoneal factor (72.5%). In 38 cases (10%), association of several other pathologies was observed. In patients with pathologies of the uterus, uterine horns (Bicornate) was the most common abnormal finding. Conclusion: In hysterosalpingography of infertile women, the most common causes of infertility were tubo-peritoneal, Multifactorial and uterine factors, respectively.